1990
DOI: 10.1002/ddr.430200302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on disposition and pharmacokinetics of drugs

Abstract: INTRODUCTION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 130 publications
2
12
0
Order By: Relevance
“…This represents a pitfall in the prediction of drug pharmacokinetics for those compounds which may demonstrate this phenomenon. Somani et al (1990) revealed that exercise has the tendency to either have no effect on or reduce the distribution volume of many drugs, a result mirrored by our simulations. Heat exposure appears to have a negligible effect on the volume of distribution of drugs, based on a review by Vanakoski and Seppälä (1998), which is the case for a number of simulated scenarios, but not all (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…This represents a pitfall in the prediction of drug pharmacokinetics for those compounds which may demonstrate this phenomenon. Somani et al (1990) revealed that exercise has the tendency to either have no effect on or reduce the distribution volume of many drugs, a result mirrored by our simulations. Heat exposure appears to have a negligible effect on the volume of distribution of drugs, based on a review by Vanakoski and Seppälä (1998), which is the case for a number of simulated scenarios, but not all (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Caffeine CL is independent of HBF [8,10] and under normal (sea level) conditions its metabolism can only be modified by changes in enzyme activity [4]. The results from this study indicate that there was a significant increase in the paraxanthine to caffeine and total MET to caffeine ratios ( Table 2) following exposure to altitude.…”
Section: Discussionsupporting
confidence: 55%
“…Indocyanine Green is a tricarbocyanine dye which is classified as a capacity limited drug [10,14]. It rapidly binds to the plasma proteins and is distributed into the plasma volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the possible influence of exercise on the DT as obtained under the EHSLC conditions, the aim of the present study was to compare the kinetic disposition of 2 test drugs in rest conditions and in conditions involving a 3 h endurance‐type exercise. As it has been reported that exercise decreases the distribution and excretion of flow‐limited drugs and increases the distribution and excretion of capacity‐limited drugs (Somani et al. 1990), dexamethasone, a drug having a rather high clearance rate and phenylbutazone, a drug with a low clearance rate, were selected as test drugs.…”
Section: Introductionmentioning
confidence: 99%